2015
DOI: 10.1128/jvi.02131-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Drug Resistance Profiles of Integrase Strand Transfer Inhibitors in Simian Immunodeficiency Virus SIVmac239

Abstract: We previously showed that the simian immunodeficiency virus SIVmac239 is susceptible to human immunodeficiency virus (HIV) integrase (IN) strand transfer inhibitors (INSTIs) and that the same IN drug resistance mutations result in similar phenotypes in both viruses. Now we wished to determine whether tissue culture drug selection studies with SIV would yield the same resistance mutations as in HIV. Tissue culture selection experiments were performed using rhesus macaque peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Notably, both G118R and R263K were found to emerge from HIV sequences in the context of dolutegravir monotherapy (6,13). We previously showed that introducing G118R in SIVmac239 integrase caused an 80% decrease in enzymatic efficiency (22,34). We also confirmed here that the SIV replicative capacity was negatively impaired by introducing the G118R substitution, whereas E92Q was mostly innocuous in this regard (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Notably, both G118R and R263K were found to emerge from HIV sequences in the context of dolutegravir monotherapy (6,13). We previously showed that introducing G118R in SIVmac239 integrase caused an 80% decrease in enzymatic efficiency (22,34). We also confirmed here that the SIV replicative capacity was negatively impaired by introducing the G118R substitution, whereas E92Q was mostly innocuous in this regard (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We have reported previously on the effects of E92Q, Q148K, G118R, and R263K on the antiretroviral drug susceptibility of SIV, as these mutations confer low-level (2-to 12-fold) resistance to DTG in vitro (22,29). Here, to explore the importance of viral fitness on treatment failure versus viral suppression, we documented the replicative capacities of wild-type (WT), E92Q mutant, and G118R mutant viruses in monkey peripheral blood mononuclear cells (PBMCs) over 12 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DTG possesses a higher genetic barrier to resistance development in comparison with RAL and EVG, and the latter two drugs share a cross-resistance profile (6-10). Simian immunodeficiency virus (SIV) and HIV-1 share similar resistance profiles against IN-resistance-associated mutations (RAMs) and similar mutational patterns emerge in SIV under drug pressure as for HIV-1 (11)(12)(13)(14).…”
mentioning
confidence: 99%